Mycotoxin elaboration in Triphala and its constituents - SINGH, PUNAM KUMARI (Indian Phytopathology, 2003)
Occurrence of mycotoxin producing fungi and potential of their toxin on the three constituents of Triphala viz., Emblica officinalis (the emblic myrobalans), Terminalia belerica (the beleric myrobalans) and T. chebula (the chebulic myrobalans) was studied. The samples were prone to natural infestation with Aspergillus flavus, A. ochraceus and Penicillium citrinum. High concentration of aflatoxin i.e. 0.08 - 0.30 µg/g in E. officinalis, 0.08 - 0.14 µg/g in T. belerica and 0.13 - 0.75 µg/gin T. chebula was recorded. Same trend was obtained in the Triphala preparation commercially available. The higher level of aflatoxin i.e. 0.98 - 1.83 µg/g in triphala besides reducing the effectiveness of the medicine, may poses serious threat to human beings due to its hepatotoxic, nephrotoxic and cytotoxic effects.